Natural Compounds With Antimicrobial and Antiviral Effect and Nanocarriers Used for Their Transportation - Stan, Diana; Enciu, Ana-Maria; Mateescu, Andreea Lorena; Ion, Andreea Cristina; Brezeanu, Ariana Cristina; Stan, Dana; Tanase, Cristiana (Frontiers in Pharmacology, 2021)
Due to the increasing prevalence of life-threatening bacterial, fungal and viral infections and the ability of these human pathogens to develop resistance to current treatment strategies, there is a great need to find and develop new compunds to combat them. These molecules must have low toxicity, specific activity and high bioavailability. The most suitable compounds for this task are usually derived from natural sources (animal, plant or even microbial). In this review article, the latest and most promising natural compounds used to combat bacteria, filamentous fungi and viruses are presented and evaluated. These include plant extracts, essential oils, small antimicrobial peptides of animal origin, bacteriocins and various groups of plant compounds (triterpenoids; alkaloids; phenols; flavonoids) with antimicrobial and antiviral activity. Data are presented on the inhibitory activity of each natural antimicrobial substance and on the putative mechanism of action against bacterial and fungal strains. The results show that among the bioactive compounds studied, triterpenoids have significant inhibitory activity against coronaviruses, but flavonoids have also been shown to inhibit SARS-COV-2. The last chapter is devoted to nanocarriers used to improve stability, bioavailability, cellular uptake/internalization, pharmacokinetic profile and reduce toxicity of natural compunds. There are a number of nanocarriers such as liposomes, drug delivery microemulsion systems, nanocapsules, solid lipid nanoparticles, polymeric micelles, dendrimers, etc. However, some of the recent studies have focused on the incorporation of natural substances with antimicrobial/antiviral activity into polymeric nanoparticles, niosomes and silver nanoparticles (which have been shown to have intrinsic antimicrobial activity). The natural antimicrobials isolated from animals and microorganisms have been shown to have good inhibitory effect on a range of pathogens, however the plants remain the most prolific source. Even if the majority of the studies for the biological activity evaluation are in silico or in vitro, their internalization in the optimum nanocarriers represents the future of “green therapeutics” as shown by some of the recent work in the field.